2020
DOI: 10.1007/s11914-020-00594-3
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy as a Treatment for Osteogenesis Imperfecta

Abstract: Purpose of Review Osteogenesis imperfecta (OI) is a chronic disease with few treatment options available. The purpose of this review is to provide an overview on treating OI with mesenchymal stem cells (MSC). Recent Findings Off-the-shelf MSC have a good safety profile and exhibit multilineage differentiation potential and a low immunogenic profile and are easy to manufacture. Their ability to migrate, engraft, and differentiate into bone cells, and also to act via para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 40 publications
0
33
0
1
Order By: Relevance
“…A number of musculoskeletal conditions such as osteoporosis, osteomyelitis, osteosarcoma, diabetic fracture and congenital disorders such as osteogenesis imperfecta result in a compromise or delay in skeletal formation/repair [ 88 , 89 , 90 , 91 ]. While a majority of reports have utilized exogenous autologous or allogeneic MSC, other studies have attempted to recruit endogenous MSC through the administration of bioactive signals, including but not limited to BMP, parathyroid hormone (PTH), C-X-C Motif Chemokine Ligand 12 (CXCL12), VEGF, PDGF-Rβ, Interleukin 10 (IL-10), and Leucine Rich Repeat Containing G Protein-Coupled Receptor 5 (Lgr5) signaling pathways, mediated by the above-mentioned biomimetic delivery methods [ 17 , 92 , 93 , 94 , 95 ].…”
Section: Bmsc Treatment For Bone Related Skeletal Diseases/disordementioning
confidence: 99%
See 2 more Smart Citations
“…A number of musculoskeletal conditions such as osteoporosis, osteomyelitis, osteosarcoma, diabetic fracture and congenital disorders such as osteogenesis imperfecta result in a compromise or delay in skeletal formation/repair [ 88 , 89 , 90 , 91 ]. While a majority of reports have utilized exogenous autologous or allogeneic MSC, other studies have attempted to recruit endogenous MSC through the administration of bioactive signals, including but not limited to BMP, parathyroid hormone (PTH), C-X-C Motif Chemokine Ligand 12 (CXCL12), VEGF, PDGF-Rβ, Interleukin 10 (IL-10), and Leucine Rich Repeat Containing G Protein-Coupled Receptor 5 (Lgr5) signaling pathways, mediated by the above-mentioned biomimetic delivery methods [ 17 , 92 , 93 , 94 , 95 ].…”
Section: Bmsc Treatment For Bone Related Skeletal Diseases/disordementioning
confidence: 99%
“…However, causative genes whose proteins normally associate with collagen also result in rare recessive forms of OI, including types V-XII and unclassified as reviewed by Marini and colleagues [ 148 ]. Depending on the severity, the pathophysiology predominantly results in reduced collagen quantity or abnormal collagen microfibril assembly, while the other causative genes influence osteoblast development, matrix mineralization and hydroxylation defects [ 91 , 148 ]. The most common clinical manifestations include abnormal skeletal development, short stature, and skeletal fragility among other non-skeletal related indications [ 93 , 149 , 150 ].…”
Section: Bmsc Treatment For Bone Related Skeletal Diseases/disordementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, preclinical studies demonstrated the potential of MSC transplantation before and after birth for severe types of OI (types II/III, severe type IV); this treatment approach is currently tested in the ongoing multicenter clinical trial boost brittle bones before birth (BOOSTB4) [ 44 ]. However, one major hurdle to such a cellular therapy is low engraftment of cells in all skeletal elements.…”
Section: Genetic Causes Of Bone Fragilitymentioning
confidence: 99%
“…Postnatal transplantation with same-donor foetal liver MSCs was performed at 1.6 years of age, and following the procedure, a resumption of vertical growth was observed. Based on these clinical experiences, the first clinical trial of the transplantation of foetal liver MSCs, the Boost Brittle Bones Before Birth (BOOSTB4) trial is ongoing [ 99 , 100 ]. The BOOSTB4 trial is investigating the safety and tolerability of MSC transplantation as a therapy for severe forms of OI (OI type 3 and 4).…”
Section: Managementmentioning
confidence: 99%